2011
DOI: 10.1080/00085030.2011.10768149
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Wounds, Severe Trauma, and Clothing, on Carcass Decomposition and Arthropod Succession in South Africa

Abstract: This study investigated the influence of different types of physical wounds as well as clothing on carcass decomposition and arthropod succession during all seasons over one year in South Africa. The trials for each season included six pigs, Sus scrofa, carcasses: two carcasses with wounds, one carcass was clothed the other was not; two carcasses with stab wounds, one carcass was clothed and the other was not; two carcasses with severe trauma wounds, one carcass was clothed and the other was not. The decomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
6
15
0
Order By: Relevance
“…The succession and development of these arthropods was very similar, with very few observations of an arthropod occurring on one carcass and not on the others. These species and succession patterns are similar to other studies conducted in the central Free State, South Africa (27,28). There appears to be a higher number of adults and maggots/larvae (both, flies and beetles, specifically C. chrysomya, C. albiceps, adults and maggots, D maculatus adults and maggots) recorded on the shaded carcasses versus the carcass exposed to full sunlight.…”
Section: Discussionsupporting
confidence: 88%
“…The succession and development of these arthropods was very similar, with very few observations of an arthropod occurring on one carcass and not on the others. These species and succession patterns are similar to other studies conducted in the central Free State, South Africa (27,28). There appears to be a higher number of adults and maggots/larvae (both, flies and beetles, specifically C. chrysomya, C. albiceps, adults and maggots, D maculatus adults and maggots) recorded on the shaded carcasses versus the carcass exposed to full sunlight.…”
Section: Discussionsupporting
confidence: 88%
“…Only two articles reported on the diversity of arthropods colonising decomposing carcasses from the southern African region 26,36 (Table 1). Kelly et al 36 observed that during the fresh stage of a pig carcass, only Musca spp.…”
Section: Arthropod Diversity During Different Stages Of Carcass Decompositionmentioning
confidence: 99%
“…Only two articles reported on the diversity of arthropods colonising decomposing carcasses from the southern African region 26,36 (Table 1). Kelly et al 36 observed that during the fresh stage of a pig carcass, only Musca spp. were found, and they persisted during the bloated stage, where seven new species (Calliphora vicina, Chrysomya chloropyga, Chrysomya marginalis, Chrysomya albiceps, Lucilia spp., Sarcophagidae and Hydrotaea capensis) visited the carcass, but did not persist past this stage.…”
Section: Arthropod Diversity During Different Stages Of Carcass Decompositionmentioning
confidence: 99%
“…early instars have difficulty penetrating intact skin, and some have reported that wounds facilitate larval establishment (Campobasso et al., ; Anderson, ). Conversely, other experimental studies have found that both perimortem (Cross & Simmons, ) and postmortem wounds (Kelly et al., ) are not used for oviposition, and female Diptera still prefer natural oviposition sites. Our research is consistent with studies showing wounds facilitating larval establishment, as treatment was found to be a significant predictor of both the first appearance and the abundance of L3.…”
Section: Discussionmentioning
confidence: 93%